Second thoughts on MIGA - Stefan Sinn (Intereconomics, 1986)
The world Bank's proposal to establish a new international organization whose purpose would be insuring foreign direct investment (FDI) against political risk was launched at its annual meeting in Seoul in October 1985. This paper is an attempt to evaluate the proposed Multilateral Investment Guarantee Agency (MIGA) from the point of view of allocation theory.
Keywords: 330; Direct Investments